2021
DOI: 10.1002/cl2.1164
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: What is the impact of complex WASH interventions on gender and social equality outcomes in low‐ and middle‐income countries? A mixed‐method systematic review protocol

Abstract: BACKGROUND 1.1 | The problem: Limited evaluation of social and gender equality outcomes of water, sanitation and hygiene interventions Safely managed water, sanitation and hygiene (WASH) services are viewed as fundamental for human wellbeing, enabling a range of positive outcomes related to health, education, livelihoods, dignity, safety, and gender equality. Progress in providing WASH services and thus achieving these outcomes has not occurred equally, with a range of inequalities in who can access and benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Detailed methodology is available in a previously published protocol. 24 However, no critical appraisal and data extraction was conducted in this review. We undertook a systematic mapping of the primary research studies instead.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed methodology is available in a previously published protocol. 24 However, no critical appraisal and data extraction was conducted in this review. We undertook a systematic mapping of the primary research studies instead.…”
Section: Methodsmentioning
confidence: 99%
“…A list of definitions of each outcome is available in online supplemental table S4 . The protocol 24 includes a detailed overview of all the theoretical assumptions used to build our theory of change, including definitions of inclusive and transformative approaches.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their distant-reading analysis of the 155 included articles, which focused only on assessment of titles and abstracts, revealed that few engaged with gender transformational-aspects of gender equality [39]. A mixed-method systematic review protocol outlines another study's planned aim and approach to synthesize evidence on gender and social equality outcomes that are specific to complex WASH interventions [43]. However, the two reviews that have been completed (Dery et al and MacArthur et al) have used methods that are limited in their scope and rigor, [44] and a need has remained for a more comprehensive synthesis of the evidence.…”
Section: Introductionmentioning
confidence: 99%